AUDIO LINGUAL METHOD TO TEACH SPEAKING AND LISTENING SKILLS IN ENGLISH FOR NURSING COURSE - Risa Arroyyani (Esteem Journal of English Education Study Programme, 2023)
The objective of this study was to create instructional techniques for teaching topics in the English for Nursing: Elementary Course using the Audio Lingual Method (ALM). The focus of the study was on developing speaking and listening skills, and the methodology used was design-based research. The study began by designing instructional materials that incorporated ALM techniques and then identifying the elements to evaluate the activities. After careful consideration, four ALM techniques were selected: repetition drill, chain drill, substitution drill, and backward build-up. These techniques were applied to three out of the eight topics covered in the English for Nursing course, specifically Parts of the Human Body, Names of Departments in the Hospital, and Nurses' Duties in Wards.